Assessment of open hole flexural strength and progressive damage mechanism of CFRP composite as a function of stacking sequence. (21st May 2021) - Gupta, Savita; Dasari, Srinivasu; Pal, Snehanshu; Prusty, Rajesh Kumar; Ray, Bankim Chandra
An experimental study was carried out to evaluate the flexural behaviour of CFRP composite laminate with introduction of open hole as well as by varying stacking sequence. Open hole is required in laminated composites to assemble the components through mechanical fasteners. Degradation in strength was observed due to the presence of a hole. Six stacking sequences have been analysed: [0]8, [90]8, [0/90]2s, [90/0]2s, [02 /902 ]s, [902 /02 ]s in which [0]8 is noticed to have highest flexural and open hole flexural strength. Strength retention is also evaluated in this study to compare retention strength of open hole laminate with laminates having no hole. Existence of both tensile and compressive failure modes during flexural loading makes overall damage mode complex. Furthermore, introduction of open hole in the laminate during flexural loading makes it more complex as variation in stress distribution activates different features of deformation and failures. Fractographic analysis has been done using scanning electron microscope to perceive damage progression mechanism during flexural loading. SEM micrographs confirmed the delamination between 90° and 0° plies as it is seen in stress strain graph as a stress drop.